Effects of winter herbage removal on Flint Hills rangeland - Lisa M. Auen; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1989)
Intensive-early stocking (lES) in the Kansas Flint Hills has greatly increased livestock production efficiency. The potential for grazing of regrowth on IES pastures the following winter was studied by mowing different plots on a monthly basis from October to April, 19831985. Winter herbage removal had no significant effect on herbage production in the following seasons or on the total nonstructural carbohydrates (TNC) of big bluestem (Andropogon gerardii) rhizomes. Since there was no reduction in herbage yield for any mowing date, cattle producers can apparently restock IES pastures after October 1.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Intensive-early stocking (lES); Winter herbage removal; Flint Hills rangeland